The Influence Of Work Motivation and Work Environment on Employee Performance In The Manufacturing Engineering Division Of PT Adis Dimension Footwear Tangerang Regency - Najmudin, Najmudin; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (Faculty of Science and Technology University of Pramita Indonesia, 2026)
This study aims to determine: (1) the partial effect of work motivation on employee performance; (2) the partial effect of the work environment on employee performance; (3) the simultaneous effect of motivation and the work environment on employee performance.This study uses a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all production employees at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 80 respondents. This study used a saturated sampling technique due to the small population size; therefore, the sample in this study used the entire population of 80 employees as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, work motivation significantly influences the performance of employees in the Manufacturing Engineering department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (2.994 >1.991) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, the work environment significantly influences the performance of employees in the Manufacturing Engineer section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (2.623 >1.991) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work motivation and work environment significantly influence the performance of employees in the Manufacturing Engineer section at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count > F table (26.994 >3.12) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that work motivation and work environment variables, both partially and simultaneously, have a significant influence on the performance of employees in the Manufacturing Engineer division at PT. Adis Dimension Footwear Balaraja-Tangerang.